Geographic and socioeconomic factors associated with leprosy treatment default: An analysis from the 100 Million Brazilian Cohort. - Kaio Vinicius Freitas de Andrade; Joilda Silva Nery; Julia Moreira Pescarini; Anna Ramond; Carlos Antônio de Souza Teles Santos; Maria Yury Ichihara; Maria Lucia Fernandes Penna; Elizabeth B Brickley; Laura C Rodrigues; Liam Smeeth; Mauricio L Barreto; Susan Martins Pereira; et al. (Public Library of Science (PLoS), 2019)
Background Although leprosy is largely curable with multidrug therapy, incomplete treatment limits therapeutic effectiveness and is an important obstacle to disease control. To inform efforts to improve treatment completion rates, we aimed to identify the geographic and socioeconomic factors associated with leprosy treatment default in Brazil. Methodology/principal findings Using individual participant data collected in the Brazilian national registries for social programs and notifiable diseases and linked as part of the 100 Million Brazilian Cohort, we evaluated the odds of treatment default among 20,063 leprosy cases diagnosed and followed up between 2007 and 2014. We investigated geographic and socioeconomic risk factors using a multivariate hierarchical analysis and carried out additional stratified analyses by leprosy subtype and geographic region. Over the duration of follow-up, 1,011 (5.0%) leprosy cases were observed to default from treatment. Treatment default was markedly increased among leprosy cases residing in the North (OR = 1.57; 95%CI 1.25-1.97) and Northeast (OR = 1.44; 95%CI 1.17-1.78) regions of Brazil. The odds of default were also higher among cases with black ethnicity (OR = 1.29; 95%CI 1.01-1.69), no income (OR = 1.41; 95%CI 1.07-1.86), familial income ≤ 0.25 times Brazilian minimum wage (OR = 1.42; 95%CI 1.13-1.77), informal home lighting/no electricity supply (OR = 1.53; 95%CI 1.28-1.82), and household density of > 1 individual per room (OR = 1.35; 95%CI 1.10-1.66). Conclusions The findings of the study indicate that the frequency of leprosy treatment default varies regionally in Brazil and provide new evidence that adverse socioeconomic conditions may represent important barriers to leprosy treatment completion. These findings suggest that interventions to address socioeconomic deprivation, along with continued efforts to improve access to care, have the potential to improve leprosy treatment outcomes and disease control.